The Cold Forming Analysis of Stainless Steel Socket-Head Screws - Yang, Chih-Cheng; Nguyen, Tu Van; Andres, Jhonel Cortez (European Journal of Applied Sciences, 2024)
A multi-stage cold forming process for the manufacture of Allen screws (I) and hexalobular socket screws (II) is studied numerically with AISI 316 stainless steel. The cold forming processes through three stages includes two upsetting operations and backward extrusion over a moving punch. The numerical simulations of cold forming are conducted using the finite element code of DEFORM-3D. The formability of the workpiece is studied numerically, such as the effect on forming load responses, maximum forming loads, effective stress and effective strain distributions and metal flow pattern. In the three-stage forming process, in the forming stages of two upsetting and one backward extrusion at the upper face of the workpiece, the effective stresses in the head of the workpiece are significantly high, and the effective strains are also significantly high due to large deformation. The maximum effective stresses of 933 MPa for the last stage of forming types (I) and (II) are the same. The effective strain responses for the last stage of forming types (I) and (II) are very similar. The flow line distributions of the last stages both for forming types (I) and (II) are also very similar, which are more severely bent and highly compacted in the zone beneath the socket cavity due to severe structure deformation. For the maximum axial forming load and forming energy, the second stage of secondary upsetting to form a larger outer diameter cylindrical head and simultaneously centering at the upper end is the largest among the three stages. The total maximum axial forming loads from the first to the last stages are 268.9kN for the three-stage forming of type (I) and 260.0kN for the three-stage forming of type (II); and the total forming energies are about 587.0J for the type (I) forming and 564.5J for the type (II) forming.